2021
DOI: 10.1186/s12969-021-00587-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between high mobility group box 1 protein and juvenile idiopathic arthritis: a prospective longitudinal study

Abstract: Objective To analyze the levels of high mobility group box 1 (HMGB1) protein on different courses of juvenile idiopathic arthritis (JIA). Methods In our prospective longitudinal study, children with JIA were included with their blood samples collected at the first visit, 1-month, 3-month, and 6-month follow-up, respectively. Samples were also collected from healthy controls and children with reactive arthritis at the first visit. Levels of HMGB1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We have previously reported significantly increased HMGB1 levels in JIA synovial fluid [ 39 ]. Recently, Xu et al [ 40 ] reported that serum HMGB1 levels at the first visit were significantly elevated in sJIA compared with other JIA subgroups. We found significantly higher HMGB1 levels in active than in inactive phases, and confirmed HMGB1’s predictive ability of sJIA activity by ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported significantly increased HMGB1 levels in JIA synovial fluid [ 39 ]. Recently, Xu et al [ 40 ] reported that serum HMGB1 levels at the first visit were significantly elevated in sJIA compared with other JIA subgroups. We found significantly higher HMGB1 levels in active than in inactive phases, and confirmed HMGB1’s predictive ability of sJIA activity by ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum HMGB–1 level was the most elevated at the time of diagnosis in patients with AOSD and SJIA, and most of the follow-up patients showed decreased levels after the disease showed an improvement. In patients with AOSD, serum HMGB–1 may be correlated with clinical disease activity, such as C–reactive protein (CRP), systemic score, skin rash, and sore throat [ 112 , 113 , 114 ]. LL–37 is released in the form of NETs via TLR 8/13 and formyl peptide receptor-like 1 in neutrophils, inducing the production of inflammatory cytokines, leading to the generation of interferon-α by dendritic cells.…”
Section: Nets In Sjia and Aosdmentioning
confidence: 99%
“…The JADAS-27 was used to evaluate the disease activity of certain JIA subgroups (oligoarticular JIA, polyarticular JIA and undifferentiated arthritis). Moreover, the Juvenile Spondyloarthritis Disease Activity Index (JSpADA) and the systemic Juvenile Arthritis Disease Activity Score (sJADAS) were used for enthesitis-related arthritis and systemic JIA, respectively [ 15 ]. Notably, the inactivity or remission of JIA was defined as JADAS ≤ 1 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the Juvenile Spondyloarthritis Disease Activity Index (JSpADA) and the systemic Juvenile Arthritis Disease Activity Score (sJADAS) were used for enthesitis-related arthritis and systemic JIA, respectively [ 15 ]. Notably, the inactivity or remission of JIA was defined as JADAS ≤ 1 [ 15 ]. 2) The screen for child anxiety Related Emotional Disorders (SCARED) was selected to evaluate the emotional status of both children and adolescents with active and inactive JIA and healthy controls [ 16 ].…”
Section: Methodsmentioning
confidence: 99%